2007
DOI: 10.1002/ajhb.20678
|View full text |Cite
|
Sign up to set email alerts
|

The changing pattern of consanguinity in a selected region of the Israeli Arab community

Abstract: The prevalence of consanguinity within the Israeli Arab community is relatively high, and is associated with high rates of inherited disorders that lead to a high frequency of morbidity and mortality. Data on consanguinity between couples were recorded during two periods (1980-1985 and 2000-2004) in relation to socioeconomic status of 4 selected villages. Two of the villages (A and B) are known to have high socioeconomic status, and the other two (C and D) are known to have low socioeconomic status. The averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 19 publications
3
29
2
Order By: Relevance
“…The mean inbreeding coefficient (F) in the present study was 0.0238. This is higher than the reported figure in a national sample of nonBedouin Arabs (F=0.192) (Jaber et al 1994) and in four selected Arab villages between 2000 and 2004 (F ranged from 0.004906 to 0.016452 according to the village) (Sharkia et al 2008).…”
Section: Discussioncontrasting
confidence: 61%
“…The mean inbreeding coefficient (F) in the present study was 0.0238. This is higher than the reported figure in a national sample of nonBedouin Arabs (F=0.192) (Jaber et al 1994) and in four selected Arab villages between 2000 and 2004 (F ranged from 0.004906 to 0.016452 according to the village) (Sharkia et al 2008).…”
Section: Discussioncontrasting
confidence: 61%
“…The results obtained in this study are in accordance with other previous studies (Na 'amnih et al, 2015;Sharkia et al, 2008). In a comparative study among three generations from Jordan, it was found that the first-cousin marriage rate also declined with time (Hamamy et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…A similar decline in the rate of consanguineous marriages was also reported in our previous research work conducted on four selected villages of the Israeli Arab community (Sharkia et al, 2008). Furthermore, other studies on Arab societies revealed a decline in the prevalence of consanguineous marriages e.g.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The prevalence of consanguineous marriages in the Arab world is considered to be much higher (35% -55%) as compared to Western countries (~1%) (Bittles, 2001;Jaber et al 1998). Recently, different studies of various Arab societies have shown that the consanguinity rates decrease with time (Hamamy et al, 2005;Khlat, 1988;Sharkia et al, 2008). Consanguinity rates in various societies were found to be dependent on multiple factors e.g.…”
Section: Introductionmentioning
confidence: 99%